2009
DOI: 10.1021/ef801021j
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Organic Acid in Bio-Oil using Acidic Ionic Liquid Catalysts

Abstract: A dicationic ionic liquid C6(mim)2−HSO4 was synthesized and used as the catalyst for bio-oil upgrading through the esterificartion reaction of organic acids and ethanol at room temperature. The reaction system turned into two layers when the reaction was complete. No coke and deactivation on the catalyst were observed. The yield of upgraded oil was about 49%, and its properties were significantly improved. The higher heating value approached to 24.6 MJ/kg, the pH value increased from 2.9 to 5.1, and the moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 39 publications
(38 reference statements)
1
46
0
Order By: Relevance
“…[29][30][31] The detailed synthesis conditions are described in the experimental section. [ À is a white solid at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] The detailed synthesis conditions are described in the experimental section. [ À is a white solid at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that dinuclear alkaline ionic liquid bis-(3-methyl-1-imidazolium-)-ethlyene dihydroxide shows excellent catalytic efficiency, the highest conversion rate of cotton seed oil was up to 98.5%, and the stability of and separation effect of the catalyst was very ideal [8]. Recently, our group still focused on the preparation of biodiesel catalyzed by ionic liquid [9,10] and reported a crystal structure of 1,1′-(hexane-1,6-diyl)bis(3-methyl-1H-imidazol-3-ium) bis(hexafluorophosphate) [11]. In order to find the ionic liquid catalyst with better catalytic efficiency we were engaged in synthesising novel ionic liquid catalysts with imidazole.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group still focused on the preparation of biodiesel catalyzed by ionic liquid [7]. In order to nd the ionic liquid catalysts with better catalytic e ciency, we were engaged in synthesising novel ionic liquid catalysts with imidazole.…”
Section: Discussionmentioning
confidence: 99%